In-store augmented reality design: fashion retail’s perspectives - Liangchao Xue; Christopher J. Parker; Cathryn Hart (2024)
Purpose: Fashion retail has faced immense changes in the rapid development of e-commerce, creating significant uncertainty about physical stores’ future. To improve the consumer shopping experience and increase sales revenue for fashion retailers, this paper investigates how Augmented Reality (AR) can be implemented within high-street fashion retail by exploring leading UK retailers’ reactions to pragmatic future scenarios.Method: This study conducted qualitative research through 13 interviews - eight retail staff from high-street and high-end markets and five AR/UX designers regarding their insights into how AR can enhance consumer engagement at each market level.Findings: The results showed that the fashion retail market is ill-prepared to use AR. AR could help high-street brands offer a seamless shopping experience for consumers by prioritising the functional purpose but exciting AR animation. This would offer consumers an efficient and enjoyable shopping experience. While implementing AR, high-end stores should tell stories through hedonic engagement, letting consumers efficiently engage with brand messages, since building an AR ecosystem is cheaper than creating the story flow physically.Originality: The study devises sixteen retailer-supported guidelines for designing AR for Fashion Retail levels to guide innovators and retailers.